Density distribution and resin migration investigations in samples of sand core made by blowing method - Dańko, Rafał; Jamrozowicz, Łukasz (AGH University of Science and Technology Press, 2017)
Resin migration in a core can occur during the core production process performed by blowing methods in which the core sand is transported into the core box as a two-phase sand-air flux characterized by various working parameters (working pressure, shooting time, volumetric concentration). This migration is the result of the resin being blown off from the matrix grain surfaces by compressed air. The methodology of the investigation of this effect developed at AGH University of Science and Technology is presented in this paper. The results of the resin migration tests obtained for cores made with cold-box technology at various working parameters of the shooting process are also shown.
Journal of Casting & Materials Engineering
Bibliogr. s. 73.
Keywords: core shooting; core blowing; molding sand; resin migration